Challenges of Electoral Malpractices on Democratic Consolidation in Nigeria's Fourth Republic - Isma'ila, Yusuf; Othman, Zaheruddin (International Review of Management and Marketing, 2016)
After a decade and half of democratic experiment yet, efforts towards democratic consolidation in Nigeria's fouth republic have been facing the challenges electoral malpractices. The crisis of democratic consolidation as a result of the challenges of electoral malpractices manifest in form of corruption, insecurity and weak democratic institutions. The significance of democratic consolidation in Nigeria like in other new democracies depends largely on the conduct of free, fair and credible election. The objective of this paper is to examine the threats of electoral malpractice as it undermines the aspiration for consolidating democracy in Nigeria's fourth republic and also use critical approach in recommending transformation of the system. Keywords: Malpractice, Consolidation, Republic and Nigeria JEL Classifications: D72, P10